What are the experiences of medical students and their trainers regarding undergraduate training in primary health care at four South African medical schools? A qualitative study - Mabuza, Langalibalele Honey; Moshabela, Mosa (Frontiers in Medicine, 2024)
Background In 1978, the World Health Organization (WHO) adopted primary health care (PHC) as the most effective strategy to meet the healthcare needs of communities. This raises the question as to the extent and nature of the training that undergraduate (UG) medical students receive in medical schools regarding PHC, following this statement. Aim The study aim was to explore the experiences of UG medical students and their trainers regarding training in PHC in their institutions. Methods A qualitative study was conducted among UG medical students (MBChB 4-6) and their trainers at four conveniently selected South African medical schools. A total of 16 focus group discussions (FGDs) and 27 in-depth interviews were conducted among students and their trainers, respectively. The MAXQDA 2020 (Analytics Pro) software program was used to arrange the data, resulting in 2,179 data segments, from which categories, sub-themes and themes were derived. Results Both the UG medical students and their trainers regarded PHC as mainly an approach to health rather than a level of care. Students were trained by specialists and generalists, received training in the undifferentiated patient, coordinated, comprehensive and continuity of care. The training in tertiary centers, conducted mainly by specialists, the implicitness of the training and the inadequacy of trainers at the PHC settings presented challenges. Conclusion Students and their trainers experienced UG student training in PHC in line with the internationally recognized principles on the subject. The view by students and their trainers that PHC is an approach rather than a level of care enhanced its training across disciplines. The implicitness of the training and the tertiary learning platforms were the main challenges experienced. For optimum PHC training, more time should be dedicated to distributed training platforms with supportive specialist outreach programs in the South African medical schools.